Mesenchymal Stem Cell-Mediated Immuno-Modulatory and Anti-Inflammatory Mechanisms in Immune and Allergic Disorders - Gugjoo, Mudasir B.; Hussain, Shahid; Amarpal; Shah, Riaz A.; Dhama, Kuldeep (Recent Patents on Inflammation & Allergy Drug Discovery, 2020)
Background: Mesenchymal Stem Cells (MSCs) are present in almost all the tissues of the body and act as the backbone of the internal tissue homeostasis. Among their various characteristic features, immuno-modulatory and/ anti-inflammatory properties play an important role in therapeutics. Objective: The current topic focuses on the characterization and immuno-modulatory and/ antiinflammatory properties of MSCs. To present and discuss the current status of MSCs immunomodulatory properties. Methods: Available literature on MSCs properties and patents have been detailed, critically interpreted, and discussed based upon available literature. The main focus has been on their characteristic immunomodulatory and anti-inflammatory properties though some of the basic characterization markers have also been detailed. The databases searched for the literature include PubMed, Med Line, PubMed Central, Science Direct and a few other scientific databases. Results: MSCs are present in a very limited concentration in the tissues, and as such their culture expansion becomes imperative. MSCs immuno-modulatory and anti-inflammatory roles are achieved through direct cell-cell contact and / by the release of certain factors. Such properties are controlled by micro-environment upon which currently very limited control can be exerted. Besides, further insights in the xeno-protein free culture media as against the fetal bovine serum is required. Conclusion: MSCs have been well-isolated, cultured and characterized from numerous tissues of the body. The majority of the studies have shown MSCs as immuno-compromised with immunomodulatory and / or anti-inflammatory properties except some of the latest studies that have failed to achieve the desired results and thus, demand further research. Further research is required in the area to translate the results into clinical application.
Keywords: culture